PENGARUH IMPLEMENTASI MATA KULIAH KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA DAN MEMBANGUN JIWA USAHA MAHASISWA JURUSAN TEKNIK SIPIL UNIVERSITAS MAHASARASWATI MATARAM - BAIQ RENI SARI DEWI (Universitas Mahasaraswati Mataram, 2018)
This study aims to determine (1) the influence of the implementation of entrepreneurship subject to the motivation of entrepreneurship of civil engineering students (2) the effect of the implementation of entrepreneurship subject to build the soul of civil engineering students. This research is a causal associative research with quantitative approach. Variables of this research are entrepreneurship subject as independent variable, motivation and build soul of business as dependent variable. Respondents in this research are students of civil Engineering Department of Mahasaraswati Mataram University amounted to 85 students. Techniques of data collection using questionnaires and documentation. Data analysis method used is simple linear regression. The results of this study indicate that (1) entrepreneurship education has a positive and significant effect on entrepreneurship motivation is shown by the value of F arithmetic 0,619 with a significance value of 0.035 and R2 0.053. (2) Entrepreneurship courses have a positive and significant impact on entrepreneurship skill by showing F value of 13,124 with significance value 0,001 and R2 0,137.